An experimental study of the dynamic properties of smart composite magnetorheological materials - Aguib, Salah; Roubah, Salah; Hadji, Mohamed; Kobzili, Lallia; Noureddine, Chikh; Djedid, Toufik (Applied Research and Smart Technology (ARSTech), 2021)
A magnetorheological is a new generation of smart materials in active mechanical vibration and shock control applications. This article is based on a comparative experimental study of the dynamic properties of magnetorheological elastomers (MRE) and magnetorheological fluids (MRF), whose damping and stiffness are controlled simultaneously by applying magnetic field intensity. The dynamic visco-analyser and rheometer were used to test the behaviour of MRE and MRF. The response of both materials depends on the amplitude due to shear strain. The experimental results clearly show the difference between the dynamic properties of MRE and MRF. More specifically, MFRs have high damping with low stiffness; on the other hand, the MRE has average damping with outstanding rigidity. These results help designers achieve more efficient and reliable structures in various engineering fields, such as buildings and mechanical applications.